KEBIJAKAN PEMERINTAH DALAM PEMBERIAN “PROPERTI” BAGI ORANG ASING DI INDONESIA PADA ERA MASYARAKAT EKONOMI ASIA (MEA) - Silviana, Ana (Diponegoro Private Law Review, 2019)
ABSTRACT  The principle of UUPA is that only Indonesian citizens can own land in Indonesia. Regarding the ASEAN economic sector (MEA) integration agenda, it has an impact on the flow of foreign natural resources into Indonesia to invest. In the land sector, of course it is related to the provision of residential property ("property") for foreign businessmen who invest in Indonesia. In this case the Government issued a policy to make it easier for foreigners to own land and / or buildings in Indonesia. PP 103 Year 2016 as a policy to provide access for foreigners to acquire property in Indonesia, revoked PP 41 of 1996 concerning Land Acquisition for Foreigners for Houses in Indonesia. The background of the issuance of PP 41 of 1996 was in the framework of implementing the provisions of Article 42 UUPA jo Article 36 PP 40 of 1996, that foreigners can have rights to land in Indonesia with the status of land using Hak Hak. It turned out that the issuance of PP 103 of 2015 was out of sync between UUPA, PP No. 40 of 1996 with PP 103 of 2015 in order to provide welfare to the Indonesian people, especially the provisions contained in Article 6 and Article 10 of PP 103 of 2015.  Key Word : Policy, Residential Ownership, Foreigner